KAJIAN YURIDIS TERHADAP KEDUDUKAN DAN KEWENANGAN KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI REPUBLIK INDONESIA - AGUS RUBIANSYAH NIM. A1011171031 (Jurnal Fatwa Hukum, 2023)
Abstract Corruption is a destructive culture that will continue to take root if it is not eradicated properly. In Indonesia, corruption is a big enemy that has not been able to be resolved. It is proven by the low Corruption Perception Index that Indonesia in 2022 is ranked 5th in ASEAN. The Corruption Eradication Commission (KPK) in carrying out its duties and authorities based on the mandate of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission.The problems studied are: "What is the position and authority of the Corruption Eradication Commission of the Republic of Indonesia?". The method used in this research is normative research method or literature study. The type of approach used is the statutory approach, the fact approach, the legal concept analysis approach, the historical approach and the comparative approach. In this study the authors collect data by literature study and case analysis.Based on the results of research conducted by the author, it can be seen that the position of the Corruption Eradication Commission as a state institution is no longer an independent institution but a state institution under executive power. This is evidenced by the existence of a new organ within the Corruption Eradication Commission, namely the Supervisory Board as a representative of the executive. The existence of the Supervisory Board is a mandate from Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission. In addition, there are also changes in the authority in dealing with corruption, both from the main and other authorities.The author in this case proposes a suggestion that the KPK's Juridical Foundation be strengthened to realize an effective and efficient KPK institution in the Indonesian constitutional system. In addition, the independence of the KPK must be returned to its original state so that the KPK can carry out its duties and functions in accordance with the mandate of democracy. The existence of the Supervisory Board which is an obstacle to the KPK must be abolished to create stability in the independence of the KPK as a quasi state institution. Then the KPK institution is expected to reappoint a number of KPK employees who were dismissed for the fulfillment of their rights that have been deprived. And in particular the Executive and Legislative institutions are expected to improve commissioner selection procedures to create commissioners with integrity in accordance with the mandate of the law. Keywords: KPK, Position and Authority, Supervisory Board, State Institution. AbstrakKorupsi merupakan budaya merusak yang akan terus mengakar apabila tidak diberantas dengan baik. Di Indonesia korupsi menjadi musuh besar yang belum mampu diselesaikan. Terbukti dengan rendah nya Indeks Persepsi Korupsi yang Indonesia ditahun 2022 menduduki peringkat 5 di ASEAN. Komisi Pemberantasan Tindak Pidana Korupsi (KPK) dalam menjalankan tugas dan wewenang berdasarkan amanat Undang-Undang Nomor 19 Tahun 2019 Tentang Perubahan Kedua Atas Undang-undang Nomor 30 Tahun 2002 Tentang Komisi Pemberantasan Tindak Pidana Korupsi.             Masalah yang diteliti yaitu: “Bagaimana kedudukan dan kewenangan Komisi Pemberantasan Tindak Pidana Korupsi Republik Indonesia ?”. Metode yang digunakan dalam penelitian ini ialah metode penelitian normatif atau studi kepustakaan. Jenis pendekatan yang digunakan yaitu pendekatang perundang-undangan, pendekatan fakta, pendekatan analisis konsep hukum, pendekatan sejarah dan pendekatan perbandingan. Dalam penelitian ini penulis mengumpulkan data dengan studi kepustakaan dan analisis kasus.            Berdasarkan  hasil penelitian yang dilakukan oleh penulis dapat dilihat bahwa kedudukan Komisi Pemberantasan Tindak Pidana Korupsi sebagai lembaga negara tidak lagi berstatus lembaga independen melainkan lembaga negara yang berada dibawah kekuasaan eksekutif. Hal tersebut dibuktikan dengan adanya organ baru dalam tubuh Komisi Pemberantasan Tindak Pidana Korupsi yaitu Dewan Pengawas sebagai representasi dari eksekuif. Keberadaan Dewan Pengawas merupakan amanat dari Undang-Undang Nomor 19 Tahun 2019 tentang Perubahan Kedua atas Undang-undang Nomor 30 Tahun 2002 tentang Komisi Pemberantasan Tindak Pidana Korupsi. Selain itu kewenangan dalam penanganan Korupsi pun juga terdapat perubahan baik dari kewenangan yang bersifat pokok maupun yang lainnya.Penulis dalam hal ini mengajukan saran agar Landasan Yuridis KPK diperkuat untuk mewujudkan kelembagaan KPK yang efektif dan efisien dalam sistem ketatanegaraan indonesia. Selain itu Independensi KPK harus dikembalikan seperti semula agar  KPK bisa menjalankan tugas dan fungsi nya sesuai dengan amanat demokrasi. Keberadaan Dewan Pengawas yang menjadi penghambat KPK harus dihapuskan untuk menciptakan kestabilan independensi KPK sebagai lembaga negara yang bersifat quasi. Kemudian untuk lembaga KPK diharapkan mengangkat kembali sejumlah pegawai KPK yang diberhentikan demi pemenuhan hak–hak mereka yang telah dirampas. Dan terkhusus lembaga Eksekutif dan Legislatif diharapkan Memperbaiki prosedur seleksi komisioner untuk menciptakan komisioner yang berintegritas sesuai dengan amanat undang-undang. Kata Kunci : KPK, Kedudukan dan Kewenangan Dewan Pengawas, Lembaga Negara.